2022
DOI: 10.1038/s41598-022-15911-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased TRIM31 gene expression is positively correlated with SARS-CoV-2 associated genes TMPRSS2 and TMPRSS4 in gastrointestinal cancers

Abstract: Besides typical respiratory symptoms, COVID-19 patients also have gastrointestinal symptoms. Studies focusing on the gastrointestinal tumors derived from gastrointestinal tissues have raised a question whether these tumors might express higher levels of SARS-CoV-2 associated genes and therefore patients diagnosed with GI cancers may be more susceptible to the infection. In this study, we have analyzed the expression of SARS-CoV-2 associated genes and their co-expressions in gastrointestinal solid tumors, cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Rapid increase in the SARS-CoV-2 infection rates worldwide resulted in an immediate response to understand the underlying mechanisms of the COVID-19 disease, including in cancer patients. Cancer patients are considered as more prone to develop COVID-19 especially because of the impaired immune system response seen in them against the SARS-CoV-2 vaccine. , Studies demonstrated that ACE2, TMPRSS2, and TMPRSS4 expression were upregulated and facilitated SARS-CoV-2 infection in tumor samples. , In addition, certain host-specific genetic factors have been shown to play a critical role in increased susceptibility to COVID-19 in cancer patients . One of the causal genes identified to be linked with COVID-19 severity was SLC6A20 gene located in the chromosome 3p21.31; , however, its link with pan-cancer tumor samples remained to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid increase in the SARS-CoV-2 infection rates worldwide resulted in an immediate response to understand the underlying mechanisms of the COVID-19 disease, including in cancer patients. Cancer patients are considered as more prone to develop COVID-19 especially because of the impaired immune system response seen in them against the SARS-CoV-2 vaccine. , Studies demonstrated that ACE2, TMPRSS2, and TMPRSS4 expression were upregulated and facilitated SARS-CoV-2 infection in tumor samples. , In addition, certain host-specific genetic factors have been shown to play a critical role in increased susceptibility to COVID-19 in cancer patients . One of the causal genes identified to be linked with COVID-19 severity was SLC6A20 gene located in the chromosome 3p21.31; , however, its link with pan-cancer tumor samples remained to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is a complex inflammatory disease and linked to an impaired immune system. Several studies have shown that cancer patients can be more susceptible to SARS-CoV-2 infection than the general population. , Although in-depth understanding of the susceptibility of cancer patients to COVID-19 is still unclear, COVID-19-associated genes, ACE2, TMPRSS2, and TMPRSS4 were upregulated and co-expressed in different cancer types. In addition to pan-cancer studies, COVID-19 susceptibility in cancer patients was explained with elevated levels of endosomal entry and recycling proteins for SARS-CoV-2 infection . Given the accumulating evidence documenting COVID-19 susceptibility in cancer patients, characterizing additional genes in these patients could contribute to identifying new targets.…”
Section: Introductionmentioning
confidence: 99%
“…Both lncRNAs and miRNAs are involved in the inflammatory cascade of scavenger receptors and subsequent regulation of the lipid metabolism pathways [ 36 ]. The expression of SCARB1 in gastric cancer tissues is significantly down-regulated, and its mechanism of action may be associated with the post-transcriptional regulation of SCARB1 mRNA by miRNA [ 7 , 29 ]. For example, during tumor occurrence, high levels of miR-199 can bind to the 3' UTR of the SCARB1 mRNA, thus inhibiting the expression of SCARB1 [ 13 , 38 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…also found that TRIM31 is positively correlated with SARS−CoV−2 associated genes TMPRSS2−TMPRSS4 and knockdown of TRIM31 significantly altered viral replication and viral processes in gastrointestinal cancer samples. This result suggests that TRIM31 may play a role in increasing the susceptibility to SARS-CoV-2 viral infection in patients with gastrointestinal cancers ( 66 ).…”
Section: Trim31: Growing Influence In Innate Immunity and Autophagymentioning
confidence: 99%